Abordagem centrada na pessoa o cuidado na preparação para o parto : conhecendo sentimentos e motivações das gestantes - Sales, Daiane Correia (2019)
The Ministry of Health (MS) established the Prenatal and Birth Humanization Program (PHPN) in 2000, in the Unified Health System, whose aims to increase access, quality and supply capacity of obstetric and neonatal care, and its principles and guidelines are intended to protect the rights of pregnant women and newborns. In this perspective, the adoption of humanized and safe practices implies the organization of routines, procedures and physical structure, as well as the incorporation of welcoming behaviors, safeguarding the dignity of women, newborns and their families, with interventions that could expose them to risks. This research intends to understand, from psychological care, the feelings and motivations of pregnant women for the choices during the preparation for childbirth. It is qualitative research of experiential approach. For theoretical and methodological reference, the Person-Centered Approach was used, proposed by Carl Rogers, adopting the modalities of group attendance and psychological on- call to collect information. The analysis was carried out using the Discursive Textual Analysis method, using the software IRAMUTEQ (Interface of Multidimensional Analyzes of Testes by Questionnaires), which assisted in the process of primary categorization of narratives. From these results, it was noticed that the feelings verbalized and experienced by the pregnant women were those of insecurity regarding the treatment received by the professionals, fear of childbirth and the experience in the hospital, as well as the uncertainty about the type of delivery desired. Thus, the motivations for the choices at the time of delivery were related to the desire to be able to experience the process intensively, with the search for the sensation of greater security and a good recovery to offer good care to your baby. According to the results, it is considered relevant to determine for pregnant-centered listening during preparation for childbirth, highlighting the importance of the use of light technologies in primary health care, with a focus on interpersonal relationships, thus favoring health promotion and avoiding the unnecessary use of harsh technologies at the time of delivery. It is notable that the facilitating attitudes used in the whole process of psychological care proved to be an important technology for the concretization of humanization, favoring the autonomy of the pregnant woman.